Cerium oxide particles with controlled microstructure
Patent Information
- Application Number
- CN202580020493.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-13
- Filing Date
- 2025-03-10
- Publication Date
- 2026-10-30
AI Technical Summary
然而,在使用此类磨料细粒的抛光方法中,由于颗粒结构具有许多边缘,因此减少划痕是一个问题
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to secondary cerium oxide particles having a controlled microstructure, which are formed by the aggregation of primary particles; to the use of these secondary particles in dispersions such as polishing slurries, particularly chemical mechanical polishing (CMP) compositions; and to methods for their preparation. Background Technology
[0002] The development of the electronics industry demands an increasing and substantial use of compositions for polishing various components, such as disks or dielectric compounds. Specifically, chemical mechanical polishing (CMP) processes are crucial for the planarization of interlayer insulating films, the formation of shallow trench isolation structures, and the formation of plugs and embedded metal wiring in semiconductor device manufacturing processes. Compositions used for this purpose are typically commercialized in dispersion form and must exhibit a number of characteristics. Specifically, they must provide a high degree of material removal, reflecting their polishing capabilities.
[0003] Typically, high removal rates can be achieved in CMP processes with large-sized abrasive particles. However, large-sized particles tend to scratch the substrate that should be polished. Therefore, the particles must also have the lowest possible defectivity; the term "defectivity" is intended to specifically refer to the number of scratches exhibited on the substrate once treated with the polishing composition.
[0004] In recent years, significant progress has been made in increasing the number of layers and the precision of semiconductor devices, and there is a growing demand for further improvements in semiconductor device yield and throughput. Therefore, there is also a growing need for scratch-free polishing compositions in CMP processes.
[0005] Polishing compositions used in CMP processes typically contain cerium oxide (CeO2) as abrasive particles. The cerium oxide particles used in such compositions come in a variety of shapes and sizes. They can be obtained through various preparation methods. One of these involves calcining and pulverizing cerium compounds (such as cerium carbonate). The cerium oxide particles thus obtained are called calcined cerium dioxide particles. However, in polishing methods using such fine abrasive particles, reducing scratches is a problem due to the numerous edges in the particle structure. For this reason, several attempts have been made, such as those described, for example, in US2 2002 / 0016060, US 2003 / 0200702, US 2009 / 0113809, or JP 2023038579 A, to reduce the number of scratches by decreasing the particle size of the cerium oxide particles while maintaining their high abrasive power.
[0006] However, there remains a need for abrasive particles suitable for CMP processes that possess high grinding capacity while avoiding scratching. Furthermore, there is a need for a method for preparing such particles that can be easily carried out on an industrial scale and ensures the acquisition of the desired particle properties. Summary of the Invention
[0007] The present invention relates to secondary cerium oxide particles having an average particle size of 100 nm or higher as determined by SEM, wherein each secondary cerium oxide particle is an aggregate of primary cerium oxide particles having an average particle size of 30 to 50 nm as determined by TEM and a crystallite size of 20 to 40 nm as determined by XRD.
[0008] In this specification, particles will be referred to as "primary particles", and aggregates of primary particles will be referred to as "secondary particles".
[0009] The terms “secondary cerium oxide particles” and “secondary particles” are used interchangeably in this document. The same applies to the terms “primary cerium oxide particles” and “primary particles”.
[0010] In addition, the present invention relates to a dispersion comprising the secondary cerium oxide particles of the present invention.
[0011] The secondary cerium oxide particles or their dispersions of the present invention can be used to prepare polishing compositions, preferably chemical mechanical polishing compositions.
[0012] Furthermore, the present invention relates to a method for preparing secondary cerium oxide particles according to the present invention, wherein the method comprises the following steps:
[0013] (i) Precipitate cerium carbonate by using cerium nitrate and ammonium bicarbonate as starting materials;
[0014] (ii) Calcine the cerium carbonate particles obtained in step (i) at 350°C to 450°C for 20 to 25 hours;
[0015] (iii) Calcine the calcined cerium carbonate particles obtained in step (ii) at 700°C to 1000°C for 0.5 to 20 hours;
[0016] (iv) Grinding the cerium oxide particles obtained in step (iii). Attached Figure Description
[0017] Figure 1 SEM images of particles obtained in Comparative Example 1
[0018] Figure 2 SEM images of particles obtained in Example 1
[0019] Figure 3 SEM images of particles obtained in Comparative Example 2
[0020] Figure 4 A schematic top view of the polished substrate, showing the locations of 12 areas inspected for defect assessment in this example. Detailed Implementation
[0021] Before describing the problems of the present invention in detail, the following should be considered:
[0022] As used herein, the singular forms “a / an” and “the” include both the singular and plural indicators, unless the context clearly indicates otherwise. For example, “a compound” means one or more compounds.
[0023] As used herein, the terms “comprising,” “comprises,” and “consisting of” are synonymous with “including,” “includes,” “containing,” and “contains,” and are inclusive or open-ended, and do not exclude additional, unlisted members, elements, or method steps. It will be understood that the terms “comprising,” “comprises,” and “consisting of” as used herein include the terms “consisting of,” “consists,” and “consists of.”
[0024] Throughout this application, the term "about" is used to indicate that a value includes the standard deviation of the error of the apparatus or method used to determine that value.
[0025] As used herein, unless otherwise specified, the term "average" refers to the exponential average.
[0026] As used herein, the terms “% by weight,” “wt.-%,” “weight percentage,” or “percentage by weight,” and the terms “% by volume,” “vol.-%,” “percentage by volume,” or “percentage by volume” are used interchangeably.
[0027] The numerical ranges listed by endpoints include all integers contained within that range, as well as fractions (where appropriate) such as 1 to 5 (which may include 1, 2, 3, 4 when referring to, for example, the number of elements, and 1.5, 2, 2.75, and 3.80 when referring to, for example, the measurement). Endpoint listings also include the endpoint values themselves (e.g., 1.0 to 5.0 includes both 1.0 and 5.0). Any numerical ranges listed herein are intended to include all subranges contained therein.
[0028] As used herein, the term "dispersion" refers to a system consisting of solid fine secondary cerium oxide particles of the present invention stably dispersed in a liquid medium, the particles possibly also optionally containing residual amounts of bound or adsorbed ions, such as nitrate or ammonium ions.
[0029] The size and size distribution of the particles of the present invention can be characterized using different parameters. Measurement methods for determining these properties are described in detail in the examples.
[0030] According to the present invention, cerium oxide (CeO2) generally has a purity of at least 99.8% by weight relative to the oxide. The cerium oxide is generally crystalline cerium oxide. Certain impurities other than cerium may be present in the oxide. These impurities may originate from raw materials or starting materials used in the process of preparing secondary cerium oxide particles. The total proportion of impurities is typically less than 0.2% by weight relative to the particles of the present invention. In this application, residual nitrates are not considered impurities.
[0031] If any disclosure of any patent, patent application, or publication incorporated herein by reference conflicts with the description of this application to the extent that it may lead to ambiguity in terminology, then this description shall take precedence.
[0032] Unless otherwise defined, all terms used in disclosing this invention (including technical and scientific terms) have the meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Further guidance is provided, including definitions of terms, to better understand the teachings of this invention.
[0033] In the following paragraphs, various alternatives, embodiments, and variations of the invention are defined in more detail. Each so-called alternative and embodiment, when the range of values for the same parameter is separated, can be combined with any other alternative and embodiment, and this applies to each variation unless explicitly stated otherwise or clearly incompatible. In particular, any feature indicated as preferred or advantageous can be combined with one or more other features indicated as preferred or advantageous.
[0034] Furthermore, in one or more embodiments, the specific features, structures, or characteristics described herein may be combined in any suitable manner as will be apparent to those skilled in the art from this disclosure. Moreover, while some embodiments described herein include certain features (among others included in other embodiments), combinations of features from different embodiments are intended to be within the scope of the invention and to form different embodiments, as will be understood by those in the art.
[0035] The present invention relates to secondary cerium oxide particles having a secondary average particle size of 100 nm or higher as determined by SEM, wherein each secondary cerium oxide particle is an aggregate of primary cerium oxide particles having an average particle size of 30 to 50 nm as determined by TEM and a crystallite size of 20 to 40 nm as determined by XRD.
[0036] The secondary cerium oxide particles of this invention can be flexibly deformed by the pressure generated by the polishing head used in the CMP process. It is believed that the buffering properties they possess due to particle deformation increase the contact between the particles and the substrate, which enhances the chemical and physical effects of the CMP process, contributing to higher removal rates while maintaining low defect rates.
[0037] According to the present invention, secondary cerium oxide particles are formed due to the agglomeration of primary particles as defined above.
[0038] The primary particles preferably have an average particle size of 35 to 45 nm, more preferably 38 to 42 nm, as determined by TEM.
[0039] The crystallite size of the primary particles according to the present invention is determined by X-ray diffraction (XRD) analysis to be between 20 and 40 nm, preferably between 21 and 35 nm, and more preferably between 25 and 35 nm.
[0040] As determined by scanning electron microscopy (SEM), the secondary cerium oxide particles formed from the primary particles of the present invention have a secondary average particle size of greater than 100 nm, more preferably at least 120 nm, and even more preferably at least 140 nm. Furthermore, it is preferred that the secondary average particle size, as determined by SEM, is at most 300 nm, more preferably at most 200 nm, and even more preferably at most 160 nm.
[0041] The specific structure of the particles according to the invention results in a specific Hg porosity for the secondary cerium oxide particles; preferably, as measured by Hg porosity for pores between 2 and 300 nm, the secondary cerium oxide particles of the invention have a pore volume of 0.10 to 0.50 ml / g, more preferably 0.15 to 0.30 ml / g, and even more preferably 0.20 to 0.28 ml / g. Not bound by this theory, the inventors believe that this porosity allows for a perfect trade-off between the necessary hardness of the secondary particles for removing a suitable amount of material from the substrate and the limitation of scratches on the substrate caused by suitable deformation of the secondary particles in the CMP process.
[0042] Further preferably, the secondary cerium oxide particles have a near-spherical shape. Particularly preferred are particles with an average sphericity of 0.70 or greater, more preferably 0.78 or greater, as measured by image analysis. Sphericity can be calculated based on the following formula:
[0043] 4π S / (L) 2 ,
[0044] Where S is the projected area of the particle measured by SEM, and L is the projected perimeter of the particle measured by SEM.
[0045] Notably, sphericity can be determined by measuring the S and L values on at least 80 particles, particularly at least 90 particles, and even more particularly at least 100 particles in the image.
[0046] The secondary cerium oxide particles of the present invention can have an oxygen storage capacity of at least 80 µmol / g, preferably at least 90 µmol / g, as determined by a temperature-programmed reduction method. Preferably, the oxygen storage capacity is between 80 and 500 µmol / g, more preferably between 100 and 250 µmol / g.
[0047] As determined using the Macsorb measuring device as described in the examples, the secondary cerium oxide particles of the present invention can exhibit a particle size of 5 to 55 μm. 2 / g, preferably 10 to 50 m 2 / g, more preferably 15 to 45 m 2 / g, or even more preferably 20 and 30 m 2 Specific surface area (BET) between / g.
[0048] The secondary cerium oxide particles of the present invention can exhibit a concentration of at least 0.063 µmol / m³. 2 Preferably at least 5.00 µmol / m 2 More preferably at least 6.00 µmol / m 2The ratio of oxygen storage capacity to specific surface area (BET) is called the "OSC / SSA ratio". Notably, the OSC / SSA ratio can be as low as 0.063 µmol / m³. 2 Up to 100 µmol / m 2 Especially 5.00 µmol / m 2 Up to 25.00 µmol / m 2 More particularly 6.00 µmol / m 2 Up to 10.00 µmol / m 2 Within the specified range. Oxygen storage capacity was determined by temperature-programmed reduction. Specific surface area was determined by the BET method. For this purpose, a device such as Macsorb, as described in the examples, can be used. The OSC / SSA ratio represents the surface reactivity of the cerium oxide particles. The higher this ratio, the higher the surface reactivity. A high OSC / SSA ratio contributes to a high removal rate. In particular, a high OSC / SSA ratio indicates a high oxygen mobility normalized by surface area. Higher oxygen mobility is a sign of higher surface reactivity, which promotes interaction with the substrate and thus increases the removal rate.
[0049] Furthermore, secondary cerium oxide particles, as determined by the measurement methods described in the examples, can in particular exhibit a hydrodynamic average diameter (Dh) of 100 to 300 nm, preferably 120 to 250 nm, and more preferably 150 to 200 nm, as determined by dynamic light scattering (DLS).
[0050] Laser diffraction can be used to characterize secondary cerium oxide particles. This technique is detailed in the examples. To determine the median diameter of secondary cerium oxide particles in powder form, a particle size analyzer is preferred. Notably, an analyzer of the Horiba type, such as the Horiba LA-920, can be used.
[0051] Therefore, the secondary cerium oxide particles of the present invention can exhibit at least one or any combination of the following characteristics:
[0052] - A median diameter D50 of 70 to 250 nm, more preferably 90 to 200 nm, and even more preferably 95 to 180 nm;
[0053] - A diameter D10 of 50 to 150 nm, more preferably 60 to 120 nm, or even more preferably 80 to 110 nm; and / or
[0054] - A diameter D90 of 80 to 400 nm, more preferably 90 to 300 nm, or even more preferably 100 to 250 nm.
[0055] Furthermore, it is preferred that the secondary cerium oxide particles have a dispersion index σ / m of less than 0.50, preferably less than 0.45, where σ / m = (D90-D10) / (2D50), and D10, D50 and D90 are determined by laser diffraction as described in the examples.
[0056] Furthermore, it is preferred that the secondary cerium oxide particles have a surface nitrate adsorption molar ratio of 0.020 to 0.050, more preferably 0.030 to 0.040, or even more preferably 0.035 to 0.038, as described in the examples.
[0057] The secondary cerium oxide particles described above can be used in dispersions.
[0058] The dispersion according to the present invention includes a liquid medium in addition to the secondary cerium oxide particles of the present invention.
[0059] The liquid medium can be water or a mixture of water and a water-miscible organic liquid. The water-miscible organic liquid should not cause secondary cerium oxide particles to precipitate or agglomerate. The water-miscible organic liquid can be, for example, alcohols such as isopropanol, ethanol, 1-propanol, methanol, 1-hexanol; ketones such as acetone, diacetone alcohol, methyl ethyl ketone; esters such as ethyl formate, propyl formate, ethyl acetate, methyl acetate, methyl lactate, butyl lactate, ethyl lactate. The water / organic liquid ratio can be between 80 / 20 and 99 / 1 (w / w).
[0060] The proportion of secondary cerium oxide particles in the dispersion can range from 0.2 wt.% to 40.0 wt.%, expressed as the weight of the secondary cerium oxide particles relative to the total weight of the dispersion. This proportion can also range from 10.0 wt.% to 35.0 wt.%. In an embodiment where the dispersion is a polishing composition, the proportion of secondary cerium oxide particles in the dispersion can more specifically be between 0.2 wt.% and 5.0 wt.%, expressed as the weight of the secondary cerium oxide particles relative to the total weight of the polishing composition.
[0061] The secondary cerium oxide particles or dispersions thereof of the present invention, as described above, can be used to prepare polishing compositions, and more particularly CMP compositions. They can be used as components of polishing compositions, and more particularly CMP compositions.
[0062] CMP compositions (or chemical-mechanical polishing compositions) are polishing compositions used to selectively remove material from the surface of a substrate. They are used in the fields of integrated circuits and other electronic devices. In practice, in the manufacture of integrated circuits and other electronic devices, multiple layers of conductive, semi-conductive, and dielectric materials are deposited onto or removed from the surface of a substrate. When material layers are sequentially deposited onto and removed from the substrate, the uppermost surface of the substrate may become uneven and require planarization. Surface planarization (or “polishing”) is the process of removing material from the substrate surface to form a generally uniform, flat surface. Planarization can be used to remove unwanted surface topography and surface defects such as rough surfaces, agglomerated material, lattice damage, scratches, and contaminated layers or materials. Planarization can also be used to form features on the substrate by removing excess deposited material used to fill features and provide a uniform surface for subsequent metallization and processing.
[0063] The substrate that can be polished with a polishing composition or a CMP composition can be, for example, a silicon dioxide substrate, glass, a semiconductor, or a wafer.
[0064] Polishing compositions or CMP compositions typically contain different components other than the secondary cerium oxide particles according to the present invention. Polishing compositions may contain one or more of the following components:
[0065] - Abrasive particles other than the secondary cerium oxide particles according to the invention (referred to herein as "additional abrasive particles"); and / or
[0066] - pH adjuster; and / or
[0067] - Surfactants; and / or
[0068] - Rheology control agents, including viscosity enhancers and coagulants; and / or
[0069] - Additives selected from carboxylic acid monomers, sulfonated monomers or phosphonated monomers and anionic copolymers of acrylates, polyvinylpyrrolidone or polyvinyl alcohol (e.g., copolymers of 2-hydroxyethyl methacrylate and methacrylic acid); nonionic polymers, wherein the nonionic polymer is polyvinylpyrrolidone or polyethylene glycol; silanes, wherein the silane is aminosilane, ureosilane or glycidylsilane; N-oxides of functionalized pyridine (e.g., N-oxides of pyridinecarboxylic acid); starch; cyclodextrins (e.g., α-cyclodextrin or β-cyclodextrin) and combinations thereof.
[0070] The pH of the polishing composition of the present invention is typically between 1 and 8. Typically, the polishing composition has a pH of 3.0 or higher. Furthermore, the pH of the polishing composition is typically 7.0 or lower.
[0071] The dispersions of the present invention can be incorporated in particular into polishing compositions disclosed in the following documents: WO 2013 / 067696, WO 2016 / 140968, WO 2016 / 141259, WO 2016 / 141260, WO 2016 / 047725, WO 2016 / 006553, WO 2021 / 081176, WO 2021 / 081171, WO 2021 / 081162, WO 2021 / 081148, WO 2021 / 081153, and WO 2021 / 081145.
[0072] The present invention also relates to a method for removing a portion of a substrate, the method comprising polishing the substrate with a polishing composition as described above.
[0073] The polishing composition according to the invention preferably has a removal rate of at least 75 nm / min, more preferably at least 80 nm / min. This can be measured according to the methods described in the examples.
[0074] The secondary cerium oxide particles of the present invention and as described above can be obtained by a preparation method comprising the following steps:
[0075] (i) Precipitate cerium carbonate by using cerium nitrate and ammonium bicarbonate as starting materials;
[0076] (ii) Calcine the cerium carbonate particles obtained in step (i) at 350°C to 450°C for 20 to 25 hours;
[0077] (iii) Calcine the calcined cerium carbonate particles obtained in step (ii) at 700°C to 1000°C for 0.5 to 20 hours;
[0078] (iv) Grinding the cerium oxide particles obtained in step (iii).
[0079] Preferably, the mixture of cerium nitrate and ammonium bicarbonate obtained in step (i) of the method of the present invention is heat-treated at a temperature of 100°C to 150°C for a period of 2 to 6 hours. Furthermore, according to the present invention, after the cerium oxide particles obtained in the grinding step (iii), these particles can be placed in a dispersion and optionally deagglomerated. This final step can noteably be carried out by milling, dual-jet treatment, or ultrasonic deagglomeration.
[0080] The preparation method of the present invention is noteworthy for the two consecutive calcination steps (ii) and (iii) of the cerium carbonate particles, especially the specific temperature conditions and calcination time used therein, which ensure that the size-uniform secondary cerium oxide particles with controlled microstructure of the present invention can be obtained after milling.
[0081] Preferably, the first calcination step (ii) is carried out at 380°C to 420°C, more preferably at 390°C to 400°C for 20 to 25 hours, and most preferably for 22 hours.
[0082] Furthermore, it is preferred that the second calcination step (iii) be carried out at a temperature of 700°C to 1000°C, more preferably 720°C to 900°C, even more preferably 750°C to 850°C, particularly preferably 770°C to 800°C for 0.5 to 20 hours, more preferably 1.0 to 15 hours, even more preferably 2.0 to 11 hours, particularly preferably 5 to 10 hours.
[0083] According to the present invention, in the first step (i) of the preparation method, cerium nitrate is mixed with ammonium bicarbonate, preferably an aqueous solution of cerium nitrate is mixed with an aqueous solution of ammonium bicarbonate. Thus, cerium carbonate precipitate is obtained.
[0084] Preferably, an aqueous solution of cerium nitrate is prepared and the aqueous solution of ammonium bicarbonate is added to the prepared cerium nitrate solution. According to an alternative and preferred embodiment, the aqueous solution of cerium nitrate is added to the aqueous solution of ammonium bicarbonate. More preferably, the cerium nitrate used has a high purity, preferably at least 99.9%.
[0085] The concentration of the cerium nitrate aqueous solution, based on cerium oxide equivalent, is preferably in the range of 150 to 450 g / L, more preferably 180 to 400 g / L, and even more preferably 200 to 350 g / L. The concentration of the ammonium bicarbonate aqueous solution is preferably 100 to 400 g / L, more preferably 120 to 400 g / L, particularly preferably 300 to 400 g / L, and particularly preferably 320 to 380 g / L. The further mixing ratio of the cerium nitrate aqueous solution and the ammonium bicarbonate aqueous solution, based on the weight ratio of cerium nitrate to ammonium bicarbonate in the aqueous solution, is preferably in the range of 1.4 to 3.0. In this case, the obtained cerium carbonate salt is, for example, Ce₂(CO₃)₃ x H₂O. The cerium carbonate salt then precipitates.
[0086] According to one specific embodiment, the medium from step (i) is further subjected to heat treatment in a temperature range of 100°C to 150°C, more preferably 120°C to 140°C, and even more preferably 132°C to 136°C for a period of 2 to 6 hours, preferably 3 to 6 hours, more preferably 3 to 5 hours, and even more preferably 3 to 4 hours. In an alternative embodiment, it can be 5 to 6 hours.
[0087] The precipitated cerium carbonate is calcined under conditions as defined above. After performing the two calcination steps (ii) and (iii), the obtained cerium oxide particles are ground to obtain secondary cerium oxide particles according to the invention. The grinding of the powder can be carried out by any method commonly used in the field of the invention. Preferably, the particles obtained after step (iii) of the method of the invention are ground in a hammer mill or a mixer. In the case of a mixer, high speeds, such as 20,000 to 25,000 rpm, can be used for short periods, such as 30 to 90 seconds.
[0088] The invention will be further illustrated by the following examples. It should be understood that the following examples are for illustrative purposes only and are not intended to limit the invention thereto.
[0089] Example
[0090] 1. Measurement of the properties of particles and their compositions
[0091] 1.1 Crystalline size
[0092] The crystallite size of the primary particles can be obtained by X-ray powder diffraction (XRD) using the Scherrer equation, as commonly used in the technical field of this invention:
[0093]
[0094] in
[0095] θ is the Bragg angle in radians.
[0096] β is the spectral broadening at half the maximum intensity (FWHM) after subtracting instrumental spectral broadening, expressed in radians.
[0097] λ is the wavelength of X-rays.
[0098] D is the size of the microcrystal.
[0099] K is a dimensionless form factor, usually fixed at 0.9.
[0100] The Scherrer equation is applied to the strongest peak located between 2θ = 27 and 29°.
[0101] 1.2 Average particle size
[0102] The average primary particle size can be determined by images obtained by TEM (transmission electron microscopy). These images must be observed using a scale and apparatus that allows for clear identification of the shape of these particles. Therefore, it is preferable to clearly distinguish these particles individually. Primary particle size is the average size of the primary particles, measured on a large number of particles (at least 80, preferably at least 90, more preferably at least 100) for statistical analysis. The scale used for observation can be, for example, in the range of 30 K to 300 K. The JEM 1400 model from JEOL, operating at 120 kV, is particularly suitable.
[0103] The average secondary particle size can be determined from images obtained by SEM (transmission electron microscopy). These images must be observed using a scale and apparatus that allows for clear differentiation of the particle shapes. Therefore, it is preferable to clearly distinguish each particle individually. The scale used for observation can be, for example, in the range of x40,000 to x500,000. A field emission SEM S-5500 from Hitachi High Technologies Corporation can be used.
[0104] 1.3 Average diameter (D10, D50 and D90)
[0105] Laser diffraction can also be used to determine the size distribution of these particles. Laser particle size analyzers such as the Horiba LA-910, 920, or 960 can be used according to the manufacturer's guidelines. For measurement, a relative refractive index of 1.7 can be used. From the volume distribution obtained by laser diffraction, various parameters commonly used in statistics, such as D10, D50, and D90, as well as the dispersion index, can be deduced.
[0106] D10 is the diameter determined by the distribution obtained by laser diffraction, in which 10% by volume of particles have a diameter smaller than D10.
[0107] D50 is the median diameter determined by the distribution obtained through laser diffraction.
[0108] D90 is the diameter determined by a distribution obtained through laser diffraction, in which 90% by volume of the particles have a diameter smaller than D90.
[0109] The “dispersion index” is defined by the following formula: σ / m = (D90-D10) / (2D50).
[0110] 1.4 Specific surface area (BET)
[0111] The specific surface area of particles can be determined by nitrogen adsorption onto the powder using the Brunauer-Emmett-Teller method (BET method). This method is disclosed in standard ASTM D 3663-03 (re-approved in 2015). The method is also described in the journal "The Journal of the American Chemical Society," 60, 309 (1938). Specific surface area can be determined using the Macsorb measuring apparatus manufactured by Mountec, by placing the sample in a glass cell, placing it in the apparatus, drying it immediately in a nitrogen atmosphere at 210°C for 30 minutes before measurement, and then measuring the BET specific surface area.
[0112] 1.5Hg porosity
[0113] Hg porosity was determined using an Autopore IV9510 analyzer.
[0114] Porosity was obtained using an autopore IV 9510 automatic mercury porosimeter following pretreatment at 210°C for 30 min, according to the manufacturer's guidelines. The sample amount was approximately 0.2 g, the mercury contact angle was 130°, and the mercury surface tension was 485 dyn / cm. From the obtained data, data relating to the pore size range of 2 to 300 nm were selected to calculate the corresponding pore volume.
[0115] 1.6 Fluid Dynamics Mean Diameter (Dh)
[0116] The hydrodynamic mean diameter can be determined using dynamic light scattering (DLS). This technique allows for the measurement of the hydrodynamic mean diameter Dh of solid objects, the value of which is affected by the presence of particle aggregates. Therefore, this measurement is typically performed on a dispersion of particles in water. Dh is determined using a Malvern Zetasizer Nano-ZS device following the manufacturer's instructions. Samples typically need to be diluted in deionized water. A dilution factor of x30,000 can be applied.
[0117] 1.7 degrees
[0118] sphericity is calculated based on the following formula:
[0119] 4π S / (L) 2 ,
[0120] Where S is the projected area of the particle measured by SEM, and L is the projected perimeter of the particle measured by SEM.
[0121] Sphericity is determined by measuring the S and L values on 100 particles in a photograph.
[0122] 1.8 Oxygen Storage Capacity
[0123] The oxygen storage capacity of particles can be measured using the temperature-programmed reduction (TPR) method.
[0124] Oxygen storage capacity (OSC) is an index that quantifies the amount of oxygen that can be released from the particle surface and bulk. OSC was obtained using a MicrotracBEL Corp. BELCATII temperature-programmed reduction analyzer, with the carrier gas consisting of 90% argon and 10% hydrogen by volume at a flow rate of 30 ml / min. The sample (0.5 g) was heated at a rate of 10°C / min.
[0125] 1.9 Surface nitrate adsorption
[0126] The amount of nitrate adsorbed on the surface can be measured by the following methods:
[0127] - Prepare 55 g of 3 wt.% diluted slurry in a 100 ml beaker by dispersing the initial powder or diluting the initial slurry in deionized water and stirring for 1 min.
[0128] - Adjust the pH of the slurry to 5 using 0.01 M NaOH;
[0129] - Adjust the slurry pH from 5 to 9 w / 0.01 M NaOH; and
[0130] - The amount of surface nitrate is calculated from the titration amount adjusted from pH 5 to 9.
[0131] 1.10 pH value
[0132] The pH value of the polishing composition at 25°C was measured using a pH meter (manufactured by Toa DenpaKogyo Co., "HM-30G"). It was the value after immersing the electrodes of the pH meter in the polishing liquid composition for 1 minute.
[0133] 1.11 Properties of the obtained particles
[0134] For each example and comparative example, X-ray diffraction patterns of the powder were prepared to confirm the characteristics of the crystalline CeO2 (sheet ASTM 34-394).
[0135] 2. Particle preparation
[0136] 2.1 Comparison Example 1
[0137] High-purity cerium nitrate (99.9% pure) was dissolved in water to prepare 1 L of an aqueous solution of cerium nitrate having a concentration of 50 g / L based on cerium oxide. This solution was added to 1 L of an aqueous solution of ammonium bicarbonate with a concentration of 150 g / L and mixed to obtain a slurry of 2300 g of cerium carbonate precipitate. The precipitate was subjected to treatment at 135°C for 1 hour. The resulting mixture was calcined at 300°C for 4 hours to give 50 g of cerium carbonate with a concentration of 100.9 m... 2 Cerium oxide powder with a specific surface area of / g was subjected to a second calcination at 800°C for 0.25 hours to obtain a sample exhibiting a surface area of 32.9 m². 2 Cerium oxide powder with a specific surface area of / g.
[0138] 2.2 Comparison Example 2
[0139] A dilute solution of cerium nitrate was prepared by adding 567 g of a 2.917 M trivalent cerium nitrate solution, 204.0 mg of a 35.5 wt.% H₂O₂ solution, and 1321.1 g of deionized water. This solution (with an H₂O₂ / Ce molar ratio of 1 / 450) was loaded into a semi-closed reservoir and then degassed by vigorous stirring and bubbling with nitrogen for 2 hours. A dilute solution of ammonia was prepared by adding 1249.0 g of deionized water and 360.1 g of a 27.1% ammonia solution. This solution was loaded into a semi-closed 3L jacketed reactor and then stirred (with a three-bladed stirrer at 300 rpm) and bubbled with nitrogen for 2 hours. The temperature of the reaction mixture was then increased to 80°C over approximately ¾ hour and maintained at this temperature for 4 hours under nitrogen purging and stirring (the stirring speed was increased from 300 rpm to 450 rpm after 25 min due to gelation). At the end of this heat treatment, the reaction mixture was allowed to cool and then acidified to pH 2 by adding 68% nitric acid. Nitrogen purging was stopped, and the suspension was finally washed by Nutsche filtration, removal of the filtered water, and resuspending the filter cake in deionized water. Several cycles of washing with deionized water filtration were performed until a conductivity of less than 0.5 mS / cm was obtained. The final suspension was adjusted to 9 wt.% relative to CeO2. The suspension was observed by SEM (see [link to SEM]). Figure 3 These particles are in the form of separate and independent primary cerium oxide particles. This is consistent with the fact that the average size of the measured secondary cerium oxide particles is very close to the average size of the primary cerium oxide particles (see Table 1).
[0140] A portion of the suspension was dried in an incubator at 200°C to obtain CeO2 powder for XRD analysis.
[0141] 2.3 Example 1 (This Invention)
[0142] A 161.2 mL solution of trivalent cerium nitrate containing 48.4 g of CeO2 was prepared in a 500 mL beaker. A 638.8 mL aqueous solution of NH4HCO3 containing 82.4 g of NH4HCO3 was prepared in a 1 L semi-closed reactor. The above cerium nitrate solution and NH4HCO3 aqueous solution were mixed with stirring over approximately 1 h. The resulting reaction mixture was diluted with deionized water to leach 1 L and then introduced into an autoclave. The reaction mixture was heated to 135°C over approximately 2 hours and maintained with stirring for approximately 3.5 hours. The reaction mixture was cooled and filtered through a Nutschee filter to obtain a filter cake. The filter cake was calcined at 400°C for 22 hours, followed by calcination at 775°C for 8 hours, and then milled at 22500 rpm for 1 minute using a mixer to obtain CeO2 powder.
[0143] Preparation of dispersions:
[0144] For DLS measurements, a slurry of CeO2 particles was prepared by adding 285 ml of a pH 4 nitric acid aqueous solution to 15 g of CeO2 powder prepared in Example 1. The slurry was then milled using φ5 mm zirconia beads and passed through a 25 µm sieve.
[0145] Dispersed dry powder:
[0146] For the secondary BET measurement, the dispersion was dried in an oven at 200°C for 15 hours to obtain a dry powder of CeO2 particles.
[0147] The physical properties of the particles obtained in Comparative Example 1 and Example 1 are shown in the attached table. “SSA” stands for “Specific Surface Area”, as measured by the BET method; OSC stands for oxygen storage capacity; OSC / SSA is the ratio of the two.
[0148]
[0149] 3. Polishing test
[0150] Slurry preparation: A slurry of CeO2 particles was prepared by adding 285 ml of a pH 4 nitric acid aqueous solution to 15 g of CeO2 powder prepared in Example 1. The slurry was then ground using φ5 mm zirconia beads and passed through a 25 µm sieve.
[0151] A slurry of particles from Comparative Example 1 was prepared in a similar manner. A slurry of particles from Comparative Example 2 was used as is.
[0152] For the polishing test, the concentration was adjusted to 1 wt.% by adding ammonia and the pH was set to 6. The polishing machine used was a Struers Tegramin-25. The surface to be polished was made of amorphous silica. The pad was cleaned with deionized water prior to polishing. The suspension was introduced into the surface to be polished at a controlled flow rate.
[0153] • Pressure applied to the head: 40 N
[0154] • Speed: 150 rpm
[0155] • Pads: Chloroprene rubber (MD-Chem) - New pads for each dispersion tested.
[0156] • Flow rate of dispersion: 6 / 20 (internal scale of polisher)
[0157] • Dispersion: The amount of cerium oxide particles is 1 wt.-%.
[0158] • pH of the dispersion: 6 (obtained by adding diluted NH4OH)
[0159] • Matrix density: 2.2 g / cm³ 3
[0160] • Base radius: 2 cm
[0161] • Polishing time: 20 minutes
[0162] The weight loss of the substrate was recorded. The first polishing run was considered as pad preparation, and only the second and third runs were used for calculation. The final weight loss value was the average of the second and third polishing runs. The removal rate (RR), expressed in nm / min, was then calculated as follows:
[0163]
[0164] in:
[0165] • Δm is the weight loss of the substrate;
[0166] • R is the radius of the base;
[0167] •ρ is the density of the substrate;
[0168] •Δt is the polishing time.
[0169] The removal rates calculated according to the present invention and from the secondary cerium oxide particles of Comparative Examples 1 and 2 are given in the following table:
[0170]
[0171] Table 2
[0172] 4. Defects
[0173] At the end of the polishing test, defects were assessed by counting the number of scratches observed on the surface of each polished substrate.
[0174] The polished surfaces were examined using a scanning electron microscope (SEM) equipped with a field emission gun (FEG) source. The instrument used was an Ultra55 from Zeiss. Images with a resolution of 1024 × 768 pixels and a pixel size of 19.53 nm were captured using an in-lens secondary electron detector operating at an accelerating voltage of 0.5 V and a working distance within the 2–3 mm range. For each sample, 12 regions were imaged, according to… Figure 4 The layout shown is evenly distributed.
[0175] The number of scratches in each imaging region was counted. The total number of scratches for each sample was determined to be the sum of the scratches in all 12 imaging regions.
[0176]
[0177] Table 3.
Claims
1. A secondary cerium oxide particle having a secondary average particle size of 100 nm or higher as determined by SEM, wherein each secondary cerium oxide particle is an aggregate of primary cerium oxide particles having an average particle size of 30 to 50 nm as determined by TEM and a crystallite size of 20 to 40 nm as determined by XRD.
2. The secondary cerium oxide particles according to claim 1, wherein, As measured by Hg porosity for pores between 2 and 300 nm, the secondary cerium oxide particles have a pore volume of 0.10 ml / g to 0.50 ml / g.
3. The secondary cerium oxide particles according to claim 1 or 2, wherein, The secondary cerium oxide particles have a size of 5 to 55 μm. 2 Specific surface area (BET) per g.
4. The secondary cerium oxide particles according to any one of the preceding claims, wherein, The secondary cerium oxide particles have a concentration of at least 5.00 µmol / m³. 2 The ratio of oxygen storage capacity to specific surface area (BET), wherein the oxygen storage capacity is determined by temperature-programmed reduction.
5. The secondary cerium oxide particles according to any one of the preceding claims, wherein, The secondary cerium oxide particles have a hydrodynamic average diameter Dh of 100 to 300 nm, determined in the dispersion by dynamic light scattering.
6. The secondary cerium oxide particles according to any one of the preceding claims, wherein, The secondary cerium oxide particles have an average sphericity of 0.70 or greater, as determined by image analysis.
7. The secondary cerium oxide particles according to any one of the preceding claims, wherein, The secondary cerium oxide particles have a median diameter D50 of 70 to 250 nm, determined by laser diffraction.
8. The secondary cerium oxide particles according to any one of the preceding claims, wherein, The secondary cerium oxide particles have a diameter D10 of 50 to 150 nm, as determined by laser diffraction.
9. The secondary cerium oxide particles according to any one of the preceding claims, wherein, The secondary cerium oxide particles have a diameter D90 of 80 to 400 nm, as determined by laser diffraction.
10. The secondary cerium oxide particles according to any one of the preceding claims, wherein, The secondary cerium oxide particles have a dispersion index σ / m of less than 0.50, preferably less than 0.
45.
11. The secondary cerium oxide particles according to any one of the preceding claims, wherein, The secondary cerium oxide particles have a surface nitrate adsorption molar ratio of 0.020 to 0.
050.
12. A dispersion of secondary cerium oxide particles according to any one of claims 1 to 11.
13. Use of the secondary cerium oxide particles according to claims 1 to 11 or the dispersion according to claim 12 for preparing polishing compositions, preferably chemical mechanical polishing compositions.
14. A polishing composition comprising secondary cerium oxide particles according to claims 1 to 11 or a dispersion according to claim 12.
15. The polishing composition of claim 14, further comprising one or more of the following components: abrasive particles other than the secondary cerium oxide particles according to any one of claims 1 to 11; and / or a pH adjuster; and / or a surfactant; and / or a rheology control agent, including a viscosity enhancer and a coagulant; and / or an additive selected from anionic copolymers of carboxylic acid monomers, sulfonated monomers or phosphonated monomers, and acrylates, polyvinylpyrrolidone or polyvinyl alcohol; a nonionic polymer, wherein the nonionic polymer is polyvinylpyrrolidone or polyethylene glycol; a silane, wherein the silane is an aminosilane, ureosilane or glycidylsilane; an N-oxide of functionalized pyridine; starch; cyclodextrin and combinations thereof.
16. A method for preparing secondary cerium oxide particles according to any one of claims 1 to 11, wherein, The method includes the following steps: (i) Precipitate cerium carbonate by using cerium nitrate and ammonium bicarbonate as starting materials; (ii) Calcine the cerium carbonate particles obtained in step (i) at 350°C to 450°C for 20 to 25 hours; (iii) Calcine the calcined cerium carbonate particles obtained in step (ii) at 700°C to 1000°C for 0.5 to 20 hours; (iv) Grinding the cerium oxide particles obtained in step (iii).
Citation Information
Patent Citations
Chemical mechanical polishing particles
JP2023038579A
Bimodal slurry system
US20030200702A1
Fine particles of oxide crystal and slurry for polishing which contains the fine particles
US20090113809A1
Additive mixture and composition and method for polishing glass substrates
WO2013067696A1
CMP polishing liquid, and polishing method
WO2016006553A1
